PENERAPAN ASAS KELANGSUNGAN USAHA DALAM PENYELESAIAN PERKARA KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAAN UTANG (PKPU) - Irianto, Catur (Jurnal Hukum dan Peradilan, 2015)
The sustainable business principles that is defined broadly and underlying the norm of bankruptcy law and the suspension payment of debt. Implementation of the principle of sustainable business is not limited to the texts that is legally regulated, but has a broader meaning which also include the whole process of bankruptcy judgement as well as payment suspension of the debt. This implementation of sustainable business principle in bankruptcy and debt payment suspension is to give positive impact in increasing the economic value of the company which will be used to pay the debt to the creditor.Keywords: Sustainable Business Principle, Bankruptcy, Suspension Payment of Debt